The Arctic & Antarctica: Scaling The Sublime, Djanogly Gallery, Nottingham UK, 23rd March - 17th June 2018. - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions. Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the Contemporary Sublime. This item contains a press release, 2 exhibition posters, and 5 exhibition views and a video of the installation work After Life . This item documents the inclusion of After Life (2016) in Scaling The Sublime: Art At The Limits Of Landscape, an exhibition of 7 artists who share concern for the landscape as a platform for shared exploration of wider narratives of scale, time and perceptual relationships to landscape. Stemming from a 2014 mixed media work Between Two Tides and the 2015 research trip to Greenland, After Life is a large multi disciplinary installation that references Caspar David Friedrichs 1824 painting Sea of Ice, consisting of a model ship trapped in constructed ice at its centre, a vitrine work, 3 wall hung screens with looped video footage of moving fragmented ice, and 4 3D images of the Arctic landscape. As part of the exhibition a panel discussion, Contemporary Art and the Landscape Sublime with participating artists was hosted by co-curator Nicholas Alfey, and a symposium was held, Scaling The Sublime that invited speakers to reflect on why landscape is a compelling subject in contemporary artThe exhibition was curated by art historian Nicholas Alfey and artist Rebecca Partridge. Photography: Images used with permission courtesy of the Djanogly Gallery. Poster and promotional material used courtesy of Lakeside Arts. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.